Antibacterial and antioxidant activities, phytochemical and toxicity analyses of ethanolic jambu bol [Syzygium malaccense (L.) Merr. and Perry] leaves extract and its application on food - Khamees, Al-Zabt Abdalrahman Mohammad (2021)
Refer to the PDF.